Intra-day ecological operation mode of hydraulic units - Vladimirovich, Lyushvin Petr; Olegovna, Buyanova Marina (IJRDO - Journal of Applied Management Science, 2021)
The fish productivity of water bodies is determined by the intensity of reproduction of sustainable replenishment, feed base, consumption, including fishing, and pollution. Under conditions of controlled runoff, hydrobionts are not evolutionarily adapted to daily changes in water level. Deposited caviar, larvae and fish dry in the floodplain and beyond the brow of the coast due to daily variability in water level - omissions. Peak omissions from coastal hydroelectric power stations lead to a premature spill of young semi-passable fish into brackish water that is disastrous for them. One of the food chains in the reservoirs begins with benthos. The development of benthos and young fish is limited by methane, the concentration of which increases to critical for them during earthquakes and floods (mass inflow from floodplains of waters and silts rich in biogas-methane).In order to preserve the fish productivity of reservoirs, it is advisable to dampen the level by separating energy, sluice and ecological passages by the time of day, prohibit explosions at reservoirs m on regional faults of the earth's crust, otherwise deduct funds for fish breeding plants, arrangement of spawning grounds and bulk reservoirs.Significant changes in the water level at high pressure dams lead to local earthquakes, massive methane emissions to reservoirs.These negative factors lead to the fact that the fish productivity of regulated reservoirs does not even go to the 20÷50% from the expected-planned level, a significant part of the population at rivers and river deltas loses food and work.